The timing of tariff structure changes in regulated industries: Evidence from England and Wales (2002)
In this paper, we investigate the dynamic evolution of tariffs in telecommunications, gas, airports, electricity and water in England and Wales. We carry out a statistical analysis of the tariffs charged by the companies, which have been subject to a price-cap since privatisation. The period covered, between 1976 and 1998, allows us to investigate systematic changes in the tariff structure before and after privatisation. In all the industries, with the exception of gas, we identify changes in the tariff structure immediately before privatisation. Some limited evidence of changes in electricity and gas tariffs before the introduction of competition is also found. © 2002 Elsevier Science B.V. All rights reserved.